Direito intertemporal tributário - Groff, Leandro Morais (2008)
The objective of this work is to analyze, using the empiric-dialectic method, the systematic behind the application of intertemporal laws pertaining to the tax matters of the Brazilian legal system, characterized by the dynamics of producing and modifying the norms whose content relates to taxation. As of the analysis of the structure of legal norms, we shall investigate the action of time on Law, the temporal conflicts between the tax norms and the solutions conceived by the Brazilian legal system to resolve them. We shall also examine how the conflicts between the tax laws affect the legal security of the citizens. We shall dedicate special attention to the importance of the principle of irretroactivity of laws in the republican form of government. Finally, we shall evaluate the tendency of the national courts as regards legal security and the principle of irretroactivity of the laws when temporal conflicts pertaining to tax laws are being resolved